2018
DOI: 10.3390/safety4020019
|View full text |Cite
|
Sign up to set email alerts
|

A Framework Based on a Systems Approach to Developing Safety Indicators in Fish Farming

Abstract: Abstract:The fish farming industry is one of the industries in Norway with the highest occupational fatality and injury rate. Despite the serious health, safety, and environmental issues in the industry, little is done to measure changes in safety over time beyond the traditional Lost Time Injury (LTI) registrations. In this article the objective is twofold; (i) to propose a framework for developing safety indicators based on Systems-Theoretic Process Analysis (STPA), and (ii) to apply the framework to find in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In addition, Holen and Utne (2018) point out that the regulatory and surveillance framework for this industry in Norway is fragmented, and gaps in the understanding of safety and health risk factors in aquaculture persist. 70 In Brazil, Speck et al (2015) identified electric shock, solar radiation, and drowning as priorities for hazard mitigation at a long-line mollusc farm. 71 Other identified hazards included noise exposure (up to 88.5 dB), biological hazards (bites, stings, zoonotic diseases), ergonomic hazards (materials handling and hazardous postures), and slip/trip/fall hazards (slippery conditions, boat travel, debris on floor).…”
Section: Us Aquaculture Sectormentioning
confidence: 99%
“…In addition, Holen and Utne (2018) point out that the regulatory and surveillance framework for this industry in Norway is fragmented, and gaps in the understanding of safety and health risk factors in aquaculture persist. 70 In Brazil, Speck et al (2015) identified electric shock, solar radiation, and drowning as priorities for hazard mitigation at a long-line mollusc farm. 71 Other identified hazards included noise exposure (up to 88.5 dB), biological hazards (bites, stings, zoonotic diseases), ergonomic hazards (materials handling and hazardous postures), and slip/trip/fall hazards (slippery conditions, boat travel, debris on floor).…”
Section: Us Aquaculture Sectormentioning
confidence: 99%
“…In the STPA analysis, it is common that the analyst has to consider a great deal of non-pertinent suggestions, resulting in waste of time and increasing the possibility of making mistakes. One way to have better results is by improving the analysis process to have more comprehensive, accurate, and relevant information [11], [12]. In addition, the execution of the STPA steps requires teamwork involving domain experts, systems engineers, and safety engineers, and other stakeholders.…”
Section: Introductionmentioning
confidence: 99%